2005
DOI: 10.1007/s10464-005-6231-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Community Violence Exposure in Adolescence

Abstract: Community violence is recognized a significant public health problem. However, only a paucity of research has examined risk factors for community violence exposure across domains relevant to adolescents or using longitudinal data. This study examined youth aggressive behavior in relation to community violence exposure among a community epidemiologically defined sample of 582 (45% female) urban adolescents. Internalizing behaviors, deviant peer affiliation, and parental monitoring were examined as moderators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 70 publications
5
83
0
6
Order By: Relevance
“…Some gender differences in exposure to violence were apparent. The finding that boys are more likely than girls to have been exposed to severe forms of community violence, especially that involving weapons, is consistent with much previous research (Lambert, Ialongo, Boyd, & Cooley, 2005) and may to some extent reflect the greater involvement of adolescent males in gang-related activities. While some existing research reports no gender difference in rates of witnessing domestic violence (Turner et al, 2006), in our sample boys appeared to be more likely than girls to witness violence between adults in the home.…”
Section: Discussionsupporting
confidence: 87%
“…Some gender differences in exposure to violence were apparent. The finding that boys are more likely than girls to have been exposed to severe forms of community violence, especially that involving weapons, is consistent with much previous research (Lambert, Ialongo, Boyd, & Cooley, 2005) and may to some extent reflect the greater involvement of adolescent males in gang-related activities. While some existing research reports no gender difference in rates of witnessing domestic violence (Turner et al, 2006), in our sample boys appeared to be more likely than girls to witness violence between adults in the home.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Brown and colleagues (1999: 94) stated that exposure to trauma has been linked with "deleterious mental health outcomes," and Paxton and colleagues (2004: 283) stated that "exposure to violence makes significant contributions to the presence of post-traumatic stress symptomatology" [italics in both quotes added for emphasis]. In light of these examples and others (Lambert et al 2005), the effect sizes observed in this study were smaller than expected. Three possible explanations for this unexpected finding are offered.…”
Section: Victimization and Mental Healthmentioning
confidence: 57%
“…For example, neighborhood economic processes, social organization, and violent crime are directly relevant for youth CV exposure. In addition, recent research has identified malleable individual characteristics (e.g., aggressive behavior, deviant peer affiliation, depressive symptoms) that predict CV exposure and may be useful intervention targets [36]. Intervention efforts also should include strategies for dealing with CV exposure.…”
Section: Discussionmentioning
confidence: 99%